A Critique of the Book Islamic Movement at North Caucasus - Seyedeh Motahare Hoseyni; Fatemeh Eidi; Razieh Mousavyfar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Anna Zelkina in her book,  entitled “Islamic Movement at North  Caucasus”, the original name of which is “In Quest for God and Freedom: The Sufi Response to the Russian Advance in the North Caucasus”, printed in London, discusses the relation between ideas and reality, especially how a religion can challenge values, social system, and cultural laws of a society. She especially attends to the effects of a mystical, political, and historical phenomenon which acted when Russian troops attacked Caucasus about 300 years ago. In this article, we study different parts of her book and discuss her view of Sufism. We also debate contextual poverty and potency of the book and introduce all the seasons of her book. As far as the structure critique is concerned, we have discussed the translational problems. The methodology of the article is documentary especially with library sources. The conclusion shows that by political view to cultural identity of Caucasian Muslims, Sufism is a way for staying in front of despotic and irreligious rulers, like Russian ones.